Personality and Developmental Characteristics of Primary School Students’ Personality Types - Yu, Yongjin; Zhang, Yanyan (Frontiers in Psychology, 2021)
Undercontrollers are socially maladaptive, with high impulsivity and an inability to adjust their self-control in relation to situational demands. The aim of this study was to investigate the personality characteristics and development characteristics of undercontrolled primary school students. In this study, the primary school students’ personality development teacher assessment questionnaire was used to evaluate the primary school students’ personality. Latent class analysis was used to classify the personality type among primary school students. One-way ANOVA was used to explore the characteristics of undercontrolled primary school students, and Chi-square test was used to investigate the grade and gender development characteristics of undercontrolled primary school students. The results show that the primary school students can be divided into three personality types: resilient, overcontrolled and undercontrolled. The score of undercontrollers is lower in the five dimensions of personality. With the growth of the grade stage, the proportion of the number of undercontrolled primary school students gradually rose to a stable trend, the proportion increased rapidly from the fourth grade, and reached the maximum in the fifth grade. The proportion of boys in undercontrolled primary school students is significantly higher than that of girls of the same type.